Rainwater harvesting system planning and design (Case study: Female dormitory building, Campus E Untirta Sindangsari) - Restu Wigati; Rama Indera Kusuma; Fahrus Sabri (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
The female dormitory building on the campus E Sindangsari Untirta, which has 161 inhabitants, needs a relatively large amount of clean water. The need is a potential application of rainwater harvesting systems (RWHS) to save water usage. Moreover, in the rainy season, the excess volume of water causes runoff to increase, while there is a lack of water in the dry season. Thus, planning this system is necessary to collect water so that rainwater is not wasted and can be used in the dry season. This study uses area calculation data with arithmetic methods and uses 90% reliable rainfall data with the F.J. method. Mock, then regarding the intensity of rain, the Mononobe theory is used. In planning the volume and design of the ground reservoir, the standard provisions of the Minister of Public Works concerning the Implementation of Non-Piping Network SPAM Development are used. 01/PRT/M2009. This study indicates that the volume of rainwater supply that can be harvested is 3124.447 m3/year, and the total water requirement of the dormitory building is 7051.8 m3/year. The RWHS in the Women's Dormitory Building consists of a ground reservoir with a capacity of 324 m3, a circle gutter with a diameter of 250 mm on the roof of the building, and a 100 mm PVC standpipe and 150 mm diameter PVC flat pipe. Based on this plan, water can be saved by an average of 41.12% per month. The calculation of the RAB of this system obtained a value of Rp. 288,471,000. Gedung asrama putri di kampus E Sindangsari Untirta yang berpenghuni 161 jiwa membutuhkan air bersih yang relatif cukup banyak. Hal ini menjadi suatu potensi penerapan rainwater harvesting system (RWHS) untuk menghemat penggunan air. Terlebih lagi, pada musim penghujan volume air berlebih menyebabkan limpasan air permukaan meningkat sedangkan pada musim kemarau terjadi kekurangan air. Dengan demikian, merencanakan sistem ini sangat diperlukan untuk menampung air sehingga air hujan tidak terbuang sia-sia dan dapat digunakan pada musim kemarau. Penelitian ini menggunakan data perhitungan kawasan dengan metode aritmatika serta menggunakan data curah hujan andalan 90% dengan metode F. J. Mock, kemudian mengenai intensitas hujan digunakan teori Mononobe. Dalam perencanaan volume dan desain ground reservoir digunakan standar ketentuan dari Permen PU Tentang Penyelenggaraan Pengembangan SPAM Bukan Jaringan Perpipaan No. 01/PRT/M2009. Hasil penelitian ini menunjukan volume suplai air hujan dapat dipanen sebesar 3124,447 m3/tahun, dan total kebutuhan air gedung asrama sebesar 7051,8 m3/tahun. RWHS pada gedung asrama putri ini terdiri dari ground reservoir berkapasitas 324 m3, talang ½ lingkaran berdiameter 250 mm pada atap gedung, dan pipa tegak PVC 100 mm serta pipa datar PVC berdiameter 150 mm. Berdasarkan perencanaan ini, penggunaan air dapat dihemat rata-rata sebesari 41,12% per bulan. Perhitungan RAB sistem ini didapatkan nilai sebesar Rp. 288.471.000.